Soybean responseto initial stage of Fusarium virguliforme infection - Giachero, María Lorena; Marquez, Nathalie; Ortega, Leandro Ismael; Ducasse, Daniel Adrian (BioRxiv, 2022)
Fusarium virguliforme causes the Sudden Death Syndrome, an important disease in soybean crops. In this work, we investigated the defensive response mechanisms in soybean root, at cell wall level, during F. virguliforme infection using an in vitro culture system. We measured total root lignin content by the acetyl bromide method and estimated the in-situ lignin and suberin deposition by confocal microscopy on local and systemic root tissues, i.e. adjacent and distant to the pathogen entry site respectively. Moreover, the expression dynamics of phenylalanine ammonia lyase (PAL), shikimate/quinate hydroxycinnamoyltransferase (HCT) and cinnamyl alcohol dehydrogenase (CAD) was evaluated by real-time quantitative PCR. The results showed that, although the most significant increment of lignin deposition was observed in the epidermal cells of local tissues, F. virguliforme also induced lignin deposition changes in a sistemic fashion. In fact, inoculated plants presented a higher deposition of lignin in hypodermis and cortex than the control ones, independently of the distance from the inoculum source, while suberin deposition was higher in local zones. Moreover, the gene expression analysis showed an up-regulation of PAL, HCT and CAD genes after the inoculation with the pathogen, which correlates with the cell wall modifications observed in the local tissues. The results presented here suggest that the increase in lignin and suberin deposition during soybean root/F. virguliforme interaction is probably a strategy not only to stop the pathogen entrance, but to provide the plant more time to prepare its defences as well.